Cav1.2 regulates osteogenesis of bone marrow‐derived mesenchymal stem cells via canonical Wnt pathway in age‐related osteoporosis. Issue 4 (23rd May 2019) - Fei, Dongdong; Zhang, Yang; Wu, Junjie; Zhang, Hui; Liu, Anqi; He, Xiaoning; Wang, Jinjin; Li, Bei; Wang, Qintao; Jin, Yan
Abstract: Aims: Age‐related bone mass loss is one of the most prevalent diseases that afflict the elderly population. The decline in the osteogenic differentiation capacity of bone marrow‐derived mesenchymal stem cells (BMMSCs) is regarded as one of the central mediators. Voltage‐gated Ca 2+ channels (VGCCs) play an important role in the regulation of various cell biological functions, and disruption of VGCCs is associated with several age‐related cellular characteristics and systemic symptoms. However, whether and how VGCCs cause the decreased osteogenic differentiation abilities of BMMSCs have not been fully elucidated. Methods: Voltage‐gated Ca 2+ channels related genes were screened, and the candidate gene was determined in several aging models. Functional role of determined channel on osteogenic differentiation of BMMSCs was investigated through gain and loss of function experiments. Molecular mechanism was explored, and intervention experiments in vivo and in vitro were performed. Results: We found that Cav 1.2 was downregulated in these aging models, and downregulation of Cav 1.2 in Zmpste24−/− BMMSCs contributed to compromised osteogenic capacity. Mechanistically, Cav 1.2 regulated the osteogenesis of BMMSCs through canonical Wnt/β‐catenin pathway. Moreover, upregulating the activity of Cav 1.2 mitigated osteoporosis symptom in Zmpste24−/− mice. Conclusion: Impaired osteogenic differentiation of Zmpste24−/− BMMSCs can be partly attributed to the decreased Cav 1.2 expression, which leads to the inhibition of canonical Wnt pathway. Bay K8644 treatment could be an applicable approach for treating age‐related bone loss by ameliorating compromised osteogenic differentiation capacity through targeting Cav 1.2 channel. Abstract : Decreased Cav1.2 expression contributes to defective osteogenic differentiation of Zmpste24−/− BMMSCs by inhibiting Wnt/β‐catenin signaling, and Bay K8644 can ameliorate osteoporosis symptom through targeting Cav1.2 channel.